1975
DOI: 10.1159/000240717
|View full text |Cite
|
Sign up to set email alerts
|

Binding of <sup>14</sup>C-Salicylic Acid and <sup>14</sup>C-PentobarbitaI to Plasma Proteins of Several Species During the Perinatal Period

Abstract: The fractional binding of 14C-salicylic acid and 14C-pentobarbital was studied as a function of age in plasma of the pig, dog, goat and human. The pig exhibited an unusual degree of hypoalbuminemia and low fractional binding of salicylic acid at birth. Albumin levels and the percent binding of salicylic acid were not significantly lower in newborn plasma than in adult plasma of the other species studied. The pig was also exceptional in that the high fractional binding of pentobarbital obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…, 1974; Morselli et al. , 1980) and in addition, pigs exhibit a pronounced degree of hypoalbuminemia at birth (Short et al. , 1975; Egeli et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1974; Morselli et al. , 1980) and in addition, pigs exhibit a pronounced degree of hypoalbuminemia at birth (Short et al. , 1975; Egeli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs display a high degree of plasma protein binding (Lees et al, 2004) and are mainly bound to albumin (Lapicque et al, 1993). The affinity of albumin for acidic drugs increases from birth into early infancy (Windorfer et al, 1974;Morselli et al, 1980) and in addition, pigs exhibit a pronounced degree of hypoalbuminemia at birth (Short et al, 1975;Egeli et al, 1998). Egeli et al (1998) found that the serum albumin concentration in 1-day-old piglets was 11 g ⁄ L and this had increased to 32 g ⁄ L by the time the piglets were 21 days old.…”
Section: Enantioselective Pharmacokineticsmentioning
confidence: 99%
“…Other compounds for which a decreased plasma protein binding has been observed in the newborn include: sulphaphenazole (Chignell et al, 197 1), sulphadimethoxine and sulphamethoxydiazine (Ganshorn and Kurz, 1968), sulphamelhoxypyrazine (Sereni et aI., 1968), benzy lpenicillin and ampicillin (Ehrnebo et aI., 1971), nafcillin (Krasner et aI., 1973), imipramine (Pruitt and Dayton, 1971), desmethylimipramine (Rane et aI., 1971) and pentobarbitone (Short et a\., 1975).…”
Section: Volume O[ Distributionmentioning
confidence: 99%